Strategi Penanganan Penyakit Budidaya Udang Vanamei (Litopenaeus Vananmei) Skala Intensif Di Kabupaten Takalar - Afandy, Alfa Astiana; Anwar, Kasful; Ridhowati, Sherly (Universitas Batangahari Jambi, 2025)
This study aims to identify the major diseases affecting whiteleg shrimp (Litopenaeus vannamei) cultivated in intensive ponds in Takalar Regency, South Sulawesi, to determine the patterns of disease distribution and outbreaks, and to formulate control strategies for intensive shrimp farming. A qualitative descriptive method was applied, with data collected through literature review, surveys, interviews, field observations, laboratory examinations, and SWOT analysis. The research was conducted in intensive shrimp farming centers in Takalar Regency, specifically in Galesong, Sanrobone, and Mangarabombang Districts. The results revealed that the main diseases affecting L. vannamei were White Spot Syndrome Virus (WSSV), Acute Hepatopancreatic Necrosis Disease (AHPND), and Enterocytozoon hepatopenaei (EHP). EHP was detected in all study sites, including Boddia, Mappakalompo, Lagaruda, and Punaga Villages, while WSSV and AHPND were found in Boddia, Lagaruda, and Punaga Villages. Disease outbreaks were more frequent during the transitional season between dry and rainy periods. Based on SWOT analysis and the strategic positioning map, the condition of shrimp farming in Takalar falls under an aggressive strategy quadrant, with the recommended approach being the S-O strategy. The recommended measures include strengthening risk-based biosecurity, increasing the use of disease-free seedstock, and optimizing routine water quality monitoring. Furthermore, government involvement is crucial in disease prevention through integrated surveillance across agencies, provision of laboratory testing facilities, and the establishment of regulations regarding the use of pharmaceuticals, chemicals, and biological agents to ensure shrimp quality meets export market requirements.